Oxidized low-density lipoproteins induce apoptosis in vascular smooth muscle cells. - Liu Wen-Lan; Guo Xun; Guo Zhao-Gui (Acta Pharmacologica Sinica; Vol 19, No 3 (May 1998): Acta Pharmacologica Sinica, 2016)
AIM: To examine whether oxidized low density lipoproteins (ox-LDL) could induce apoptosis in rabbit aortic smooth muscle cells (VSMC). METHODS: Low density lipoproteins (n-LDL) were isolated from healthy human plasma by gradient ultracentrifugation and oxidized by CuSO4 10 mumol.L-1. VSMC were exposed to ox-LDL, n-LDL, or phosphate-buffer solution (PBS) as control. Morphological changes were observed under fluorescene microscope after Hoechst 33258 staining. Extracted DNA was electrophoresized on agarose gel. RESULTS: Incubation of VSMC with ox-LDL 300 mg.L-1, not n-LDL, for 24 h induced morphological apoptosis changes (chromatin condensation, nucleus fragmentation) and DNA fragmentation, which was furthered with the incubation time up to 48 h or at a concentration of 400 mg.L-1. Dextran sulfate, a scavenger receptor blocker and butylated hydroxytoluene (BHT), an antioxidant, exhibited no effect on DNA fragmentation. Lysophosphatidylcholine (LPC) at a concentration up to 125 mumol.L-1 (equivalent to ox-LDL 300 mg.L-1) did not elicit DNA fragmentation. CONCLUSION: Ox-LDL induced apoptosis in VSMC without involving oxygen free radicals and LPC.